Receiving each other's gifts - Sattler, Dorothea; Nüssel, Friederike (Studia liturgica, 2024)
Using the example of the Lord's Supper and the eucharist, this article seeks to show the conditions which make a common liturgical celebration a gift of God to the community of believers in Jesus Christ. The form chosen is a dialogue between two theologians, both members of the German “Ecumenical Study Group of Protestant and Catholic Theologians”: Friederike Nüssel (Protestant, Heidelberg) and Dorothea Sattler (Roman Catholic, Münster). The focus is the group’s study “Together at the Lord's Table.” Based on extensive research the study group has formulated the vote to be invited to join in the celebration of the eucharist and the Lord's Supper, trusting in the self-giving presence of Jesus Christ. Ecumenical sensitivity in the shaping of liturgies is an obvious consequence. Individual confessional traditions have preserved an asset that others today can experience as a gift in the form of a reminder of the common origin: the celebration with shared bread and the chalice offered to all (in the background is the controversy over the lay chalice), the binding lectionaries and the remembrance of the dead. The criticism of the vote of the Ecumenical Study Group, especially from the Roman Catholic doctrinal side, primarily relates to the topics of ministry and understanding of the church. The Ecumenical Study Group advocates that eucharistic celebrations be led by duly ordained persons. The contribution is framed by introductory remarks on basic questions of ecumenical hermeneutics and by an outlook on the great importance of interdisciplinary theological study work from an ecumenical perspective.